Development of local-wisdom based writing e-module at elementary school - Turahmat Turahmat; Andi Maulana; Muhamad Afandi; Puguh Ardiyanto Iskandar (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
This study aims to develop a local wisdom-based writing e-module at the Sultan Agung Jepara Islamic Elementary School. This study uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The first stage is needs analysis, followed by e-module design, module development, and elementary school student group trials. After that, evaluation and revision are carried out based on the input received. The results of the study indicate that the developed e-module is effective in improving the writing skills of elementary school students. The use of this e-module has also succeeded in increasing elementary school students' awareness of the importance of maintaining and preserving local wisdom in everyday life. The trial also showed an increase in the motivation of elementary school students in participating in writing learning, with higher enthusiasm. From the results of this study, it can be concluded that the local wisdom-based writing e-module at Sultan Agung Jepara Islamic Elementary School can be an interesting and effective learning alternative, which not only improves the writing skills of elementary school students, but also introduces them to important local cultural values.